2021
DOI: 10.1088/1742-6596/1779/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Multimedia Communication for Physical Distancing in Physical Education

Abstract: Education is a sector that needs to go on to operate countinously as a means of student’s activity and development in covid-19 pandemic. Multimedia is the best solution for managing PE class not to stop despite the social distancing issue. The aduance of technology in digitalization era isn’t an obstacle to on going learning activities. Advance multimedia facility could surely be able to answer the problem arising in the society related to physical activity carried out as a form of learning. The efectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…The entrepreneurship research status of students in sports majors is as follows. Adi et al ( 2021 ) found that empowering leadership is positively correlated with the feedback of followers seeking in the innovation and development of enterprises; feedback-seeking of employees is positively related to task performance, responsible person, and right to speak, and it mediates the positive relationship between empowering leadership and task performance, as well as a responsible person and right to speak. Brieger et al ( 2021 ) studied the individual psychological adaptation of entrepreneurs using a questionnaire.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The entrepreneurship research status of students in sports majors is as follows. Adi et al ( 2021 ) found that empowering leadership is positively correlated with the feedback of followers seeking in the innovation and development of enterprises; feedback-seeking of employees is positively related to task performance, responsible person, and right to speak, and it mediates the positive relationship between empowering leadership and task performance, as well as a responsible person and right to speak. Brieger et al ( 2021 ) studied the individual psychological adaptation of entrepreneurs using a questionnaire.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wasit sepakbola biasanya berotasi pada 3 area utama lapangan yaitu zona tengah dan dua zona akhir lapangan kedua tim yang bertanding (Darren, R. Scoot, J. Stevens, & J Dascombe, 2014). Kebugaran yang prima juga menjadi indikator untuk seseorang dapat maksimal tampil dilapangan (Adi et al, 2021), wasit sepak bola menuntut fisik yang kuat dengan menempuh jarak sekitar 11 km selama pertandingan dengan perkiraan 3,0 km pada intensitas tinggi lebih dari 14,4 km/Jam (Coutts & Reaburn, 2000). Wasit memiliki tingkatan level mulai dari lesensi, jam terbang, dan juga kapasitas intelegensi seperti wasit sepak bola di liga Australia kategori elit harus memiliki pengalaman memimpin pertandingan rata-rata 5.000 pertandingan yang sudah dijalani untuk mendapatkan kategori wasit yang memenuhi standar untuk bertugas diliga utama (Catteeuw, Gilis, Jaspers, Wagemans, & Helsen, 2010).…”
Section: Pendahuluanunclassified
“…Dengan rutinitas berolahraga dapat mengurangi depresi, stress, kecemasan, meningkatkan percaya diri, kualitas istrahat, dan kemampuan berkonsentrasi. Pada masa pandemic saat ini disarankan untuk tetap melakukan aktivitas ditempat umum dengan Pyhsical distancing (Adi et al 2021).…”
Section: Pendahuluanunclassified